2014
DOI: 10.1186/1745-6215-15-312
|View full text |Cite
|
Sign up to set email alerts
|

Reducing depression during the menopausal transition: study protocol for a randomised controlled trial

Abstract: BackgroundThe menopausal transition (MT) is a biological inevitability for all ageing women that can be associated with changes in mood, including depressive symptoms. There is tentative evidence that women who develop depression during the MT have greater risk of subsequent depressive episodes, as well as increased health morbidity and mortality. Thus, preventing depression during the MT could enhance both current and the future health and well-being of women. This study aims to test the efficacy of a client-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…All of these factors may interact to facilitate the development of depressive symptoms during the menopause transition. [11] The transition through menopause can be a challenging and difficult time with many co-factors that exacerbate anxiety and depression, therefore, clinicians need to be alert to the conditions and provide an environment where discussion and referral for psychological support can be considered to manage symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors may interact to facilitate the development of depressive symptoms during the menopause transition. [11] The transition through menopause can be a challenging and difficult time with many co-factors that exacerbate anxiety and depression, therefore, clinicians need to be alert to the conditions and provide an environment where discussion and referral for psychological support can be considered to manage symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…26 In terms of the limitations of this research, while the Beck questionnaire is a valuable resource for assessing the prevalence and intensity of depression and anxiety, it may not be an appropriate tool for differentiating between anxiety and depression within the general population. 27 Our study only considered women who reported experiencing natural menopause, thus our results may not be generalizable to women who undergo menopause through surgical intervention or other causes.…”
Section: Discussionmentioning
confidence: 97%
“…In terms of the limitations of this research, while the Beck questionnaire is a valuable resource for assessing the prevalence and intensity of depression and anxiety, it may not be an appropriate tool for differentiating between anxiety and depression within the general population. 27 …”
Section: Discussionmentioning
confidence: 99%